Dimensi Epistemologis Tafsir al-Qur’an Aktual Karya KH. Musta’in Syafi’i - Ahmad Zaiyadi (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2019)
This article attempts to reveal epistemological dimension of Musta’in Syafi’i’s interpretation in his work Tafsir al-Qur’an Aktual. It employs the perspective of truth theory which has been widely known within the philosophy of science. As a product of interpretation, Musta’in’s work has been a result of scientific work whose validity can be critically evaluated on the basis of three standards of truth, namely coherence, correspondence, and pragmatic aspect covered in the work. The study finds that the validity of interpretation of Musta’in is measurable. The measurability of this work can be seen within its coherence in presenting propositions systematically, logically, and consistently. The coherence of propositions and argumentative facts show us that Musta’in’s work is correspondently accurate. Musta’in’s work, moreover, is pragmatically advantageous as it corresponds to scientific expediency when it worthily contributes to provide the society solutions and answers to their social problems and other aspects regarding Islamic laws.